Functional, textural, and sensory properties of milk protein concentrate-based supercritical fluid extrudates made with acid whey - Ashton K. Yoon; Syed S.H. Rizvi (International Journal of Food Properties, 2020)
The worldwide Greek yogurt market is a growing multi-billion-dollar industry in need of a solution for its environmentally problematic acid whey byproduct. This study evaluated the effects of concentrated Greek acid whey (GAW) substituted in lieu of water during extrusion of milk protein concentrate-based snacks. Water, unhydrolyzed GAW, and hydrolyzed GAW were used as the three liquid sources during extrusion and physicochemical, textural, and sensory properties of the extrudates were evaluated. Addition of GAW significantly (P < .05) increased extrudate radial expansion ratio (RER) and porosity and decreased piece density. GAW generally improved textural characteristics of hardness, crispness, and crunchiness or produced extrudates comparable to commercial products. A consumer sensory acceptance test showed that GAW significantly improved hedonic and Just About Right (JAR) scores in all four attribute categories. The results indicate GAW’s potential to replace water during extrusion, simultaneously utilizing an environmentally undesirable byproduct while improving extruded snack foods.